The thickness of radar-bright deposits in Mercury’s northern hemisphere from individual Mercury Laser Altimeter tracks - Susorney, Hannah C. M. (Icarus, 2019)
The discovery of Mercury’s radar-bright deposits has expanded our understanding of volatiles in the solar system. Key to deciphering the history and origin of the radar-bright deposits is an estimate of the volume of radar-bright material that in turn requires a measure of the average thickness of the deposits. In this study we investigate changes in topography across radar-bright deposits hosted in flat-floored, complex craters using individual edited Mercury Laser Altimeter (MLA) tracks. We compare the difference in heights of radar-bright regions and non-radar-bright regions of the crater floor and the difference of similarly sized and located regions in non-radar-bright craters and show that the two populations cannot be distinguished. The similarity of topography in these two sets of craters allows an upper limit of 15 m to be placed on the thickness of the radar-bright deposits.